Dynamics of Islamic Theological Thought Development in the Classical Period - Zaini, Muhammad; Fauziah, Mira (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
The discourse surrounding the issue of classical Islamic theology that has developed so far is: First, that the emergence of schools in Islamic theology was predominantly due to political factors, even though if explored more deeply it turns out that differences in methods of thinking were the main factor; Second, there is an assumption that mutaqaddimin scholars understand theological verses in the Koran textually and do not understand them rationally, even though in reality many Muslim theologians interpret these theological verses rationally and freely. Based on these two issues, this article will reveal the dynamics of Islamic theological thinking of Islamic scholars in the classical period. The aim is to find the significance of the influence of the thinking activities of Muslim theologians during the classical period on the growth and development of Islamic theological thought and the birth of firqahs in Islamic theology during that period.